Sustainable Audience Loyalty in Digital Public Broadcasting: An Integrated Analysis Using SEM and Two Fuzzy-Set Delphi Approach in Thailand - Thanasom, Bhakanundh; Pankham , Sumaman (Journal of Posthumanism, 2025)
This study examines the key factors driving sustainable audience loyalty for Public Broadcasting Services in Thailand (Thai PBS) through an innovative Two Fuzzy Set Delphi Technique and Structural Equation Model (SEM), filling a crucial research gap by offering a new perspective on audience loyalty that extends beyond the Technology Acceptance Model (TAM) in digital broadcasting. Using a mixed-methods approach, qualitative data were gathered from 21 experts through in-depth interviews using the two fuzzy set Delphi techniques, while quantitative data were collected via an online survey of 818 Thai PBS audiences. The findings demonstrate that the proposed model has a good fit with empirical data, identifying eight factors that affect sustainable audience loyalty: trust, attitude, social media use, perceived ease of use, perceived usefulness, intention to view, social media engagement, and sustainable loyalty. This study suggests that Thai PBS should focus on increasing audience engagement, building trust through reliable content, and providing user-friendly features to help maintain audience loyalty. This framework will be a roadmap for the THAI PBS to gain sustainable audience loyalty while fulfilling its public service mission.